The Model of Strategies Employed by English Teachers in Teaching Writing Skill in National Plus Schools - Astrini, Febri; N.M, Ratminingsih,; G.A. L.P, Utami, I. (LPPM Undiksha, 2020)
In teaching writing, there are number of strategies that can be used. This study was intended to explore (1) the teaching writing strategies used by the teacher, (2) the differences in teaching, and (3) the problems encountered by the English teacher in teaching writing skill. This study was a descriptive qualitative study. Teachers from Bintang Mandiri and Widyatmika Junior High Schools were involved as the informant of the study. They were observed during the teaching and learning process and also interviewed. The data taken from observation and interview were analyzed in order to find out the answer the research questions. It was identified that In Bintang Mandiri the teacher used 1 more teaching writing strategy namely creative writing while in Widyatmika, creative writing was not identified. There were three main problems identified from the teachers. The first was students’ difficulties in expressing ideas in English. The second problem was students’ grammar. The third was students’ passiveness in classroom. Suggestions and implications are furtherly discussed.